Five Rings: Enclosing the London 2012 Olympic Games. Issue 1 (28th August 2013) - Gardner, Jonathan
Abstract : Considering the successive iterations of the fence surrounding the London 2012 Olympic site in Stratford, east London, I demonstrate that during the five periods of enclosure considered, these boundaries have highlighted the London Games' contested past, present, and future. An examination of the material and discursive constructions of each of these boundaries shows the Janus-faced nature of their relationship to the wider 'mega-event'. I conclude that though the purpose of such enclosures may initially seem obvious, in actuality they, as parts of a wider assemblage, can act unpredictably both to support and challenge the Olympic brand and its existence in this part of east London.